Bulk Universality for Unitary Matrix Models - Poplavskyi, M. (Журнал математической физики, анализа, геометрии, 2009)
A proof of universality in the bulk of spectrum of unitary matrix models, assuming that the potential is globally C² and locally C³ function (see Theorem 1.2), is given. The proof is based on the determinant formulas for correlation functions in terms of polynomials orthogonal on the unit circle. The sin-kernel is obtained as a unique solution of a certain nonlinear integrodifferential equation without using asymptotics of orthogonal polynomials.